Incidence and Predictors of Progression to Chagas Cardiomyopathy: Long-Term Follow-Up of Trypanosoma cruzi–Seropositive Individuals. Issue 19 (9th November 2021) - Nunes, Maria Carmo P.; Buss, Lewis F.; Silva, Jose Luiz P.; Martins, Larissa Natany A.; Oliveira, Claudia Di Lorenzo; Cardoso, Clareci Silva; Brito, Bruno Oliveira de Figueiredo; Ferreira, Ariela Mota; Oliveira, Lea Campos; Bierrenbach, Ana Luiza; Fernandes, Fabio; Busch, Michael P.; et al.
Abstract : Background: There are few contemporary cohorts of Trypanosoma cruzi –seropositive individuals, and the basic clinical epidemiology of Chagas disease is poorly understood. Herein, we report the incidence of cardiomyopathy and death associated with T. cruzi seropositivity. Methods: Participants were selected in blood banks at 2 Brazilian centers. Cases were defined as T. cruzi –seropositive blood donors. T. cruzi –seronegative controls were matched for age, sex, and period of donation. Patients with established Chagas cardiomyopathy were recruited from a tertiary outpatient service. Participants underwent medical examination, blood collection, ECG, and echocardiogram at enrollment (2008–2010) and at follow-up (2018–2019). The primary outcomes were all-cause mortality and development of cardiomyopathy, defined as the presence of a left ventricular ejection fraction <50% or QRS complex duration ≥120 ms, or both. To handle loss to follow-up, a sensitivity analysis was performed using inverse probability weights for selection. Results: We enrolled 499 T. cruzi –seropositive donors (age 48±10 years, 52% male), 488 T. cruzi –seronegative donors (age 49±10 years, 49% male), and 101 patients with established Chagas cardiomyopathy (age 48±8 years, 59% male). The mortality in patients with established cardiomyopathy was 80.9 deaths/1000 person-years (py) (54/101, 53%) and 15.1 deaths/1000 py (17/114, 15%) in T. cruzi –seropositive donors with cardiomyopathy at baseline. Among T. cruzi –seropositive donors without cardiomyopathy at baseline, mortality was 3.7 events/1000 py (15/385, 4%), which was no different from T. cruzi –seronegative donors with 3.6 deaths/1000 py (17/488, 3%). The incidence of cardiomyopathy in T. cruzi –seropositive donors was 13.8 (95% CI, 9.5–19.6) events/1000 py (32/262, 12%) compared with 4.6 (95% CI, 2.3–8.3) events/1000 py (11/277, 4%) in seronegative controls, with an absolute incidence difference associated with T. cruzi seropositivity of 9.2 (95% CI, 3.6–15.0) events/1000 py. T. cruzi antibody level at baseline was associated with development of cardiomyopathy (adjusted odds ratio, 1.4 [95% CI, 1.1–1.8]). Conclusions: We present a comprehensive description of the natural history of T. cruzi seropositivity in a contemporary patient population. The results highlight the central importance of anti– T. cruzi antibody titer as a marker of Chagas disease activity and risk of progression. Abstract : Supplemental Digital Content is available in the text.